Analisis Pengembangan Sistem Informasi Dengan Metode Waterfall Systematic Literature Review - Qolbi, Ramdhan Maulana; Putra, Reza Maulana; Nugroho, Wahyu (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
Information system development is currently experiencing rapid growth involving various platforms such as mobile, web and desktop. This often causes confusion in choosing the appropriate platform because each has advantages and disadvantages. This research aims to analyze the waterfall method model in information system development using data from various related journals. The method applied in this research is Systematic Literature Review (SLR), which is used to collect data from a number of relevant studies. The waterfall method offers a clear and organized structure, which makes project management and documentation easier. Thus, the waterfall method is the right choice in situations where project needs and specifications can be predicted from the start. Additionally, waterfall allows each stage to be completed before moving on to the next, minimizing the risk of changes during the development process. The research results show that the waterfall method is suitable for use both for new system creation projects and for large-scale system or software development.